Controlling the Chromaticity of White Organic Light‐Emitting Diodes Using a Microcavity Architecture. Issue 1 (13th November 2019) - Jeong, Soyeong; Jung, Suhyun; Kang, Hongkyu; Choi, Sang‐Bae; Hong, Soonil; Lee, Jinho; Yu, Kilho; Kim, Nara; Kee, Seyoung; Lee, Dong‐Seon; Lee, Kwanghee
Abstract: The tailoring of the chromaticity of white organic light‐emitting diodes (WOLEDs) has presented a significant challenge in their application in smart lighting sources to improve the quality of life and human performance. Here, a new microcavity WOLED (M‐WOLED) structure to modulate the chromaticity of the emitted light is demonstrated by only adjusting the thickness of the white light‐emitting layer. By introducing a polymer‐metal hybrid electrode that functions both as a partially reflective mirror and a transparent electrode, a very simple microcavity architecture that does not require additional outer mirrors, such as distributed Bragg reflectors is developed. The resulting M‐WOLEDs exhibit reddish‐, greenish‐, and bluish‐white colors with different thicknesses of the single white light‐emitting layer. Abstract : A very simple microcavity architecture is developed by introducing a polymer–metal hybrid electrode that functions both as a partially reflective mirror and a transparent electrode. The resulting M‐white organic light‐emitting diodes exhibit reddish‐, greenish‐, and bluish‐white colors with different thicknesses of the single white light‐emitting layer.